Time, Space, Memory: Chronotopic Views of Architectural Restorations in the Late Roman Empire - Andrew Ruff (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
This empirical investigation seeks to understand formally, experientially, and graphically the processes of late Roman restoration, its influences, its meanings, and its effects. As spatial conditions of these restorations exist solely in a realm of experience, my research attempts to convey the formal narrative of these monuments and express the original intention of subsequent restoration efforts. Mikhail Bakhtin’s theory of the chronotope serves as the basis of my spatial and temporal analysis, although I have taken the liberty to extrapolate the idea of the chronotope from a static intersection in space-time to a truly dynamic relationship between the diverse existences of a single act of architecture within its historical context. The ruin, the restoration, and the destruction of these architectural monuments all hold implications about the social, political, and aesthetic hierarchies of fourth and fifth century Rome, as well as inferring a discourse of architecture as a critical component of the political spectrum.
Keywords: Architectural Restorations; Chronotope; Roman Empire